2016
DOI: 10.18535/ijsshi/v3i9.24
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Innovation in Sustainable Competitive Advantage in Universities in Kenya

Abstract: Purpose-The purpose of this research was to assess the role of organizational innovation in sustainable competitive advantage of universities in Kenya. Specifically, the study examined the role of product innovation, administration innovation, and process innovation in sustainable competitive advantage of universities in Kenya. Design/methodology/approach-The paper adopted a cross-sectional survey design to generate quantitative data to test the research hypotheses. Stratified random sampling technique was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The three components of organizational innovation as identified by Kising'U, et al (2016) are: Administrative Innovation, Product Innovation, Process innovation) .Therefore, the research paper will discuss organizational innovation in accordance with the finding of Kising'U, et al (i.e., the three components of organizational innovation) (Kising'U, et al, 2016) …”
Section: Organizational Innovationmentioning
confidence: 78%
See 3 more Smart Citations
“…The three components of organizational innovation as identified by Kising'U, et al (2016) are: Administrative Innovation, Product Innovation, Process innovation) .Therefore, the research paper will discuss organizational innovation in accordance with the finding of Kising'U, et al (i.e., the three components of organizational innovation) (Kising'U, et al, 2016) …”
Section: Organizational Innovationmentioning
confidence: 78%
“…Also The organizational commitment of the organizations will enhance the organizational innovation as instilling the spirit of belonging to the employee pays him to stay in and contribute to the success of the organization This result is supported by a study that was conducted by Singh (2016) who concluded that the quality of internal service has a significant impact on the performance and satisfaction of employees. Furthermore, Several studies have indicated that the importance of organizational innovation in improving performance and improving the financial performance of banks (Kising'u et al, 2016;Fadil et al, 2016;Hsieh, 2004;Oria & Kibait.,2016).…”
Section: Discussion Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Teece and Pisano [53] and Teece et al [54] suggested that the winners in the global market are companies that demonstrate timely responsiveness and innovation that is fast and flexible [55,56], together with management's ability to coordinate effectively and re-apply internal and external competencies [57]. However, Miranda and Figueiredo [58] distinguish routine and innovative companies based on technological innovation capabilities with the factors that shape vision and strategy capabilities [51,52], utilization of competency bases, organizational intelligence, creativity and idea management, organizational structures and systems, culture and climate and technology management [53]. Saunila defines innovation capabilities by influencing an organization's ability to manage innovation [53].…”
Section: Distinctive Innovation Capability and Firm Performancementioning
confidence: 99%